ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP ANGKATAN KERJA DI JAWA TENGAH MENGGUNAKAN PENDEKATAN MULTIPLE LINIER REGRESSION - Naili Makarima; Moh Yamin Darsyah (Universitas Muhammadiyah Semarang, 2017)
The employment issue is one of the main issues that developing countries must confront as well as Indonesia. The increasing number of people without offsetting the increase in employment is a trigger for the proliferation of unemployment. Therefore, it is necessary to research about what factors are the triggers and bring a great influence on employment in Central Java seen from the Labor Force Participation Rate, Gross Regional Domestic Revenue and Population. This research uses secondary observation data with observation unit of Regency and City in Central Java Province using Multiple Linear Regression method. After research on the influence of factors that have a great influence on unemployment rate in Central Java, it is found that the Population, GRDP, and Labor Force Participation rate negatively affect the Labor Force in Central Java Province.Keywords: Ketenagakerjaan, Tenaga Kerja, Angkatan Kerja, Multiple Linier Regression